Embodied Finance: A Conceptual Framework for Agency, Value, and Trust - Chiappino, Simone (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
The diffusion of artificial intelligence (AI) and platform architectures is transforming financial services beyond the mere technical integration of banking functionalities. While research on embedded finance emphasizes modularity, it offers limited insight into how systems evolve when AI-driven inference and platform environments jointly structure financial action. This paper introduces embodied finance as a relational–informational configuration in which services take form through interactions among humans, machines, and platforms. Drawing on information systems (IS), cognitive science, and platform economics, the proposed framework—the machine–platform–crowd triangle—reframes agency, trust, and value as emergent properties rather than institutional attributes. Agency is conceptualized as distributed enactment, value as identity-based informational persistence arising from uncertainty reduction, and trust as network-mediated expectation stabilization. The framework outlines illustrative proxies and a system-level observability lens, thereby enabling the distinction between embodied configurations and embedded integrations and supporting future empirical research on adaptive, AI-enabled financial systems.